Here we all are - DePaola, Tomie, 1934- (New York : G.P. Putnam's Sons, 2000)
Children's author-illustrator Tomie De Paola describes his experiences at home and in school when he was a boy.
Last page is numbered 26.
Wilson's Children.
Pub Weekly.
Booklist.
4.6
3-6
Keywords: DePaola, Tomie, -- 1934- -- Childhood and youth -- Juvenile literature; DePaola, Tomie, -- 1934- -- Homes and haunts -- Connecticut -- Meriden -- Juvenile literature; DePaola, Tomie, -- 1934- -- Childhood and youth; DePaola, Tomie, -- 1934-; Authors, American -- 20th century -- Biography -- Juvenile literature; Authors, American; Illustrators; American authors -- Biography; Authors, American -- Biography; Illustrators -- Biography; Meriden (Conn.) -- Biography -- Juvenile literature; Meriden (Conn.) -- Social life and customs -- Juvenile literature; Meriden (Conn.) -- Biography; Meriden (Conn.) -- Social life and customs; Family life -- Connecticut -- Biography